МАТЕМАТИКА ДАРСЛАРИДА ДИДАКТИК ТАМОЙИЛЛАРДАН ФОЙДАЛАНИШ - Шукуров, Х.Г. (SCIENCE and SOCIETY, 2021)
ness of materials is the distinguishing feature of math lessons. Students will qualitatively comprehend the materials, if a teacher is able to: purposefully organize their performance during lessons, attract students to study materials by showing their acquirement and knowledge, demonstrate purpose and goal of the tasks, create a good behavior educational environment. The following article is made in order to create educational changes that can be used to conduct this kind of lessons.